Evaluation of Pathologic Complete Response in Breast Cancer Patients Treated with Neoadjuvant Chemotherapy: Experience in a Single Institution over a 10-Year Period - Misun Choi; Yeon Hee Park; Jin Seok Ahn; Young-Hyuck Im; Seok Jin Nam; Soo Youn Cho; Eun Yoon Cho (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Background Pathologic complete response (pCR) after neoadjuvant chemotherapy (NAC) has been associated with favorable clinical outcome in breast cancer patients. However, the possibility that the prognostic significance of pCR differs among various definitions has not been established. Methods We retrospectively evaluated the pathologic response after NAC in 353 breast cancer patients and compared the prognoses after applying the following different definitions of pCR: ypT0/is, ypT0, ypT0/is ypN0, and ypT0 ypN0. Results pCR was significantly associated with improved distant disease-free survival (DDFS) regardless of the definition (ypT0/is, p = .002; ypT0, p = .008; ypT0/is ypN0, p < .001; ypT0 ypN0, p = .003). Presence of tumor deposits of any size in the lymph nodes (LNs; ypN ≥ 0(i+)) was associated with worse DDFS (ypT0 ypN0 vs ypT0 ypN ≥ 0(i+), p = .036 and ypT0/is ypN0 vs ypT0/is ypN ≥ 0(i+), p = .015), and presence of isolated tumor cells was associated with decreased overall survival (OS; ypT0/is ypN0 vs ypT0/is ypN0(i+), p = .013). Residual ductal carcinoma in situ regardless of LN status showed no significant difference in DDFS or OS (DDFS: ypT0 vs ypTis, p = .373 and ypT0 ypN0 vs ypTis ypN0, p = .462; OS: ypT0 vs ypTis, p = .441 and ypT0 ypN0 vs ypTis ypN0, p = .758). In subsequent analysis using ypT0/is ypN0, pCR was associated with improved DDFS and OS in triple-negative tumors (p < .001 and p = .003, respectively). Conclusions Based on our study results, the prognosis and rate of pCR differ according to the definition of pCR and ypT0/is ypN0 might be considered a more preferable definition of pCR.